2021
DOI: 10.1002/wsb.1241
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to Waterfowl Hunting by Hunters and Anglers in the Central United States

Abstract: Waterfowl hunting participation has been on the decline since the mid‐1980s. We used a web‐based survey to better understand waterfowl hunting constraints (i.e., factors that limit or prohibit participation and enjoyment in leisure activities) among hunters and anglers that hunted or did not hunt waterfowl in the central United States. Forty‐eight constraint items were condensed into 10 constraint factors: Rules and Regulations, Waterfowl Identification, Cost, Waterfowl Hunting Skills, Land Access and Permissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Conservation organizations (e.g., DU, Delta Waterfowl, Pheasants Forever, National Wild Turkey Federation) may also provide opportunities to enhance skills through mentorship and access to resources needed to participate in hunting, such as equipment and land (Larson et al 2014). Lack of access to land is often cited as a constraint to active participation in hunting (Metcalf et al 2015, Gruntorad and Chizinski 2020, Hinrichs et al 2021 a ). The network connections provided by conservation organizations may help hunters negotiate these constraints, which could support increased hunting opportunities and participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation organizations (e.g., DU, Delta Waterfowl, Pheasants Forever, National Wild Turkey Federation) may also provide opportunities to enhance skills through mentorship and access to resources needed to participate in hunting, such as equipment and land (Larson et al 2014). Lack of access to land is often cited as a constraint to active participation in hunting (Metcalf et al 2015, Gruntorad and Chizinski 2020, Hinrichs et al 2021 a ). The network connections provided by conservation organizations may help hunters negotiate these constraints, which could support increased hunting opportunities and participation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, state agencies and conservation organizations have hired recruitment, retention, and reactivation (R3) coordinators and have implemented R3 efforts to increase hunter numbers through college student recruitment programs and experimental regulations (Council to Advance Hunting and the Shooting Sports and Wildlife Management Institute 2016, Hinrichs et al 2021 b , Vayer et al 2021). Additionally, researchers have devoted more attention to better understanding the social factors (e.g., motivations, constraints, satisfaction, preferences) influencing waterfowl hunters, other outdoor recreationists, and conservationists (Schroeder et al 2019, Shipley et al 2019, Wilkins et al 2019, Hinrichs et al 2021 a , b ). For example, NAWMP partners conducted a series of workshops and surveyed hunters and bird watchers in the United States and Canada to assess the experiential preferences of new recruits, those who identified themselves as hunters or bird watchers, and finally, those who contributed to conservation (Harshaw 2018 a , b ; Slagle and Dietsch 2018 a , b ).…”
mentioning
confidence: 99%
“…Our results suggest that, overall, elk hunters in Nebraska had the most difficulty negotiating constraints pertaining to social interactions with landowners and by limited opportunities to harvest elk due to elk occurring on property inaccessible to the hunter. Many Nebraska elk hunters view the lack of access to game as one of their greatest constraints, as access to land (Hinrichs et al 2021 a ) and harvest opportunity is routinely cited as one of the most important determinants of hunter satisfaction (Gigliotti 2000, Frey et al 2003, Schroeder et al 2018). By increasing public or private land access, management agencies may provide more areas to hunt and indirectly decrease conflicts among hunters (potentially increasing harvest success; Fontaine et al 2019, Wszola et al 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that attitudes, preferences, motivations, and expectations of waterfowl hunters are interconnected (Schroeder et al 2019, Hinrichs et al 2021b, and that hunting experiences are sensitive to intrapersonal (awareness and interest), interpersonal (mentoring and guidance), and structural (access to equipment) conditions , Hinrichs et al 2021a, Vayer et al 2021.…”
mentioning
confidence: 99%
“…Previous research has demonstrated that attitudes, preferences, motivations, and expectations of waterfowl hunters are interconnected (Schroeder et al 2019, Gruntorad et al 2020, Hinrichs et al 2021b), and that hunting experiences are sensitive to intrapersonal (awareness and interest), interpersonal (mentoring and guidance), and structural (access to equipment) conditions (Gruntorad and Chizinski 2020, Hinrichs et al 2021 a , Vayer et al 2021). In sport participation, factors such as years of experience, age at initiation to the activity, and motivation for participation have an effect on an athlete's ability to perform (Baker et al 2003).…”
mentioning
confidence: 99%